Dampak Penggunaan Pembayaran Digital terhadap Kepuasan dan Loyalitas Konsumen UMKM Makanan di Kabupaten Badung Provinsi Bali - Hayyun Aini (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Although most food MSMEs have adopted digital payment systems, insufficient understanding of the impact of digital payment usage on consumer satisfaction and loyalty may hinder food MSMEs in Badung Regency from leveraging technology to enhance competitiveness and business sustainability. With increasing competition and changing consumer behavior that prioritizes convenience and efficiency, it is essential for MSMEs to understand the factors influencing consumer satisfaction and loyalty to improve their business performance and growth.This study aims to analyze the effect of digital payment on loyalty, the effect of digital payment on satisfaction, the effect of satisfaction on loyalty, and the mediating effect of satisfaction on the relationship between digital payment and loyalty. The results indicate that digital payment significantly influences loyalty and satisfaction, satisfaction significantly affects loyalty, and digital payment has an indirect effect on loyalty through satisfaction as a mediating variable.